Ethics, love, and faith in Kierkegaard : philosophical engagements - Mooney, Edward F., 1941- (Indiana series in the philosophy of religion., 2008)
This volume collects essays from 13 leading scholars that center on key themes that characterize Kierkegaard's philosophy of religion.